Two interpenetrating 3D MOFs constructed by bis(imidazole) and V-shape carboxylate co-ligands: synthesis, structure, gas adsorption and photoluminescent properties. Issue 17 (1st September 2016) - Lu, Jiu-Fu; Liu, Zhi-Hong
Abstract: Two 3-D MOFs, {[Co2 (oba)2 (bmip)]·DMA}n (1 ) and [Cd(1, 3-bdc)(bmip)]n (2 ), where H2 oba = 4, 4′-oxybis(benzoic acid), 1, 3-bdc = isophthalic acid and bmi p  = 1, 3-bis(2-methylimidazolyl)propane, were synthesized under solvothermal conditions and characterized by single-crystal X-ray diffraction, powder XRD, FT-IR, TGA, and elemental analysis. Complex1 features a 3-D→3-D twofold interpenetrating framework, and topological analysis shows the framework can be described as a 6-connected uninodal pcu net having the point symbol (4 12 .6 3 ). Complex2 shows a 3-D→3-D threefold interpenetrating network that can be described as a 4-connected uninodal cds net with (6 5 .8) topology. Gas adsorptions of1 were carried out, and photoluminescent properties of1 and2 were also investigated at room temperature. Abstract :